Aktivitas Imunomodulator Ekstrak Buah Mengkudu pada Mencit yang Diinfeksi Staphylococcus aureus (IMMUNOMODULATORS ACTIVITY OF NONI (MORINDA CITRIFOLIA L.) FRUIT EXTRACT IN MICE INFECTED WITH STAPHYLOCOCCUS AUREUS) - Mufidah, Zumrotul; Rifa’i, Muhaimin; Rahayu, Sri (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
This study aim was to determine the immunomodulatory activity of noni (Morinda citrifolia L.) fruitextract in mice infected with Staphylococcus aureus. Mice were divided into two group :  non-infected  andinfected. Non Infected group was without S. aureus infection whereas the infected group was infected withS. aureus. Group contain control, dose 1 (25 mg/kg BW), dose 2 (100 mg/kg BW), and dose 3 (300 mg/kg BW).Oral treatment carried out for 20 days in every morning and each sample was injected with  S. aureus atday 21 with 109 cell/mL. Relative number of T cell (CD4+, CD4+CD25+),) and cytokine interferon-ã fromCD4+ T cell (CD4+IFN-ã+) subsets was measured using the BD FACSCaliburTM Flowcytometer. Data wereanalyzed by using Analysis of Varians (p<0,05) and SPSS 16 for windows. The result showed thatadministration of noni crude extract was significantly change the relative number of CD4+, CD4+IFN-ã+,and CD4+CD25+ T cells. Treatment of noni crude extract in non-infection group could increase  relativenumber of CD4+, CD4+IFN-ã+  and CD4+CD25+ T cells that might be caused by active compounds of noni asmitogen.  Giving of noni crude extract in infected group could reduce  the relative number of CD4+, CD4+CD25+and CD4+IFN-ã+ T cells due to it  active compounds as anti-inflamation. Noni fruit extract can be used aspreventive therapy on S. aureus infection  because it contains active compounds as an anti-inflammationeffect.
Keywords: Morinda citrifolia, Staphylococcus aureus, immunomodulators